PREVALENCE OF TEMPOROMANDIBULAR DISORDERS AMONG PATIENTS VISITING A PRIVATE DENTAL INSTITUTION - A., Ashwatha Pratha; Chaudhary, Manjari; Kumar Jain, Ravindra (International Journal of Psychosocial Rehabilitation, 2020)
Temporomandibular disorders (TMD) are a set of joint and muscular dysfunctions of the cranio-orofacial area. Thus the diagnosis of early symptoms and sign of Temporomandibular Disorders during adolescence is fundamental for preventing or minimizing TMD pain. Aim of the study is to investigate the prevalence of temporomandibular disorders among patients visiting Saveetha Dental College. A retrospective cross-sectional study was conducted using the patient's record from Saveetha Dental College from June 2019 to March 2020. Patients selected by non-probability purposive sampling. Data was collected and then subjected to statistical analysis. Higher prevalence of Temporomandibular patients is seen in the age group of 30-40yrs (43%) and female (51%) population. Within the limits of study, higher prevalence of Temporomandibular patients is seen in the age group of 30-40yrs in male population with TMD Disc condyle disorders. Extensive study should be done with more sample population and improved ways of diagnosis. The aim of the study was to create awareness among people regarding the advantage of early intervention of Temporomandibular disorders.